The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: on the measurement of growth rate using galaxy correlation functions. Issue 2 (11th April 2017) - Satpathy, Siddharth; Alam, Shadab; Ho, Shirley; White, Martin; Bahcall, Neta A.; Beutler, Florian; Brownstein, Joel R.; Chuang, Chia-Hsun; Eisenstein, Daniel J.; Grieb, Jan Niklas; Kitaura, Francisco; Olmstead, Matthew D.; et al.
Abstract: We present a measurement of the linear growth rate of structure, f, from the Sloan Digital Sky Survey III (SDSS-III) Baryon Oscillation Spectroscopic Survey (BOSS) Data Release 12 (DR12) using convolution Lagrangian perturbation theory (CLPT) with Gaussian streaming redshift space distortions (GSRSD) to model the two-point statistics of BOSS galaxies in DR12. The BOSS-DR12 data set includes 1198 006 massive galaxies spread over the redshift range 0.2 <  z  < 0.75. These galaxy samples are categorized in three redshift bins. Using CLPT-GSRSD in our analysis of the combined sample of the three redshift bins, we report measurements of f σ8 for the three redshift bins. We find f σ8  = 0.430 ± 0.054 at z eff  = 0.38, f σ8  = 0.452 ± 0.057 at z eff  = 0.51 and f σ8  = 0.457 ± 0.052 at z eff  = 0.61. Our results are consistent with the predictions of Planck Λ cold dark matter-general relativity. Our constraints on the growth rates of structure in the Universe at different redshifts serve as a useful probe, which can help distinguish between a model of the Universe based on dark energy and models based on modified theories of gravity. This paper is part of a set that analyses the final galaxy clustering data set from BOSS. The measurements and likelihoods presented here are combined with others in Alam et al., to produce the final cosmological constraints from BOSS.